Advanced Structural and Chemical Imaging - Browning, Nigel D.; Holzenburg, Andreas; Moeck, Peter; Koch, Christoph T.
Advanced Structural and Chemical Imaging (ASCI) serves as an interdisciplinary forum covering the entire field of advanced imaging. Particularly welcome are multi-modal studies exploring the links among imaging, diffraction, spectroscopy, data processing, and large-scale data analysis for the purpose of elucidating structure-function and structure-property relationships in atomic and molecular systems. The journal provides a dedicated platform for knowledge sharing among scientists using these imaging and analysis techniques but who may be unaware of important developments in complementary sub-fields. Coverage includes the emerging area of dynamic imaging at various orders of magnitude in spatial and temporal resolution from microns to angstroms and from milliseconds to femtoseconds. With the common need to deliver high-quality images and analyses using multiple imaging tools, forefront data handling, and mathematical methods for processing and simulations in fields as diverse as physics, chemistry, molecular and cell biology, pharmaceutical science, and materials science and engineering, ASCI brings together methods and results that are currently spread over many discipline- or technique-specific journals.Topics appropriate to the journal include but are not limited to: Structural analysis of organics, membrane proteins, and macromolecules Structural analysis of cell organelles and membrane microdomains Structural analysis of inorganics and nanocrystals Structural analysis of crystalline surfaces and interfaces, 2D crystallography, surface reconstructions Full chemical analysis of crystalline phases by combining atomic level structural and spectroscopic analyses Polycrystal orientation and phase mapping/analysis, texture and interface analyses at the nanometer length scale Large scale microscope data acquisition and processing Reconstruction algorithms for 3-D imaging and compressed sensing. ASCI was founded in 2013 by Nigel D. Browning, Andreas Holzenburg, Wolfgang Neumann and Peter Moeck.